CYCERON O POLITYKU, FILOZOFIE I POLITYCE - Nieć, Mateusz (Zeszyty Prawnicze, 2016)
Cyceron about Politician, Philosopher and Politics Summary I analize Cyceronian concept of politician and philosopher, two ideas Arpinata present in famous political treatise the „Republic”. Concept of politician is part of political tradition in republic Rome, idea of philosopher expressing authoritative tradition in Hellada. Since III century b. Ch. both ideas have clashed. Politician is modern style of thinking; politician (and politics) are a city (republic), whereas philosopher is traditional style of thinking, philosopher is a village (monarchy). Cyceronian concept of statesman I descriptioned by Platonian theory of the cycle.